2006
DOI: 10.1007/11926078_29
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Conjunctive Triple Pattern Queries over Large Structured Overlay Networks

Abstract: We study the problem of evaluating conjunctive queries composed of triple patterns over RDF data stored in distributed hash tables. Our goal is to develop algorithms that scale to large amounts of RDF data, distribute the query processing load evenly and incur little network traffic. We present and evaluate two novel query processing algorithms with these possibly conflicting goals in mind. We discuss the various tradeoffs that occur in our setting through a detailed experimental evaluation of the proposed alg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(71 citation statements)
references
References 24 publications
0
71
0
Order By: Relevance
“…Similar to [14,15], triple patterns are adopted as the basic units of user queries in our system. A triple pattern is an expression of the form (s, p, o) where s and p are URIs or variables, and o is a URI, a literal or a variable.…”
Section: Preliminariesmentioning
confidence: 99%
“…Similar to [14,15], triple patterns are adopted as the basic units of user queries in our system. A triple pattern is an expression of the form (s, p, o) where s and p are URIs or variables, and o is a URI, a literal or a variable.…”
Section: Preliminariesmentioning
confidence: 99%
“…Query processing is based on so-called query chains, which mainly resemble a sequential processing strategy. In [54], the authors also propose a variant that exploits the values of matching triples found while processing the query incrementally by constructing multiple chains for each query. This introduces some limited degree of parallelism into query processing.…”
Section: Related Workmentioning
confidence: 99%
“…), researchers have also studied parallel and distributed solutions for RDF(S) reasoning and query processing. Recent proposals in this area have been based on distributed hash tables (DHTs) [14,15,16,17,9,18], distributed computing platforms based on powerful clusters [19,20,21,22] and cloud computing platforms using MapReduce [23].…”
Section: Introductionmentioning
confidence: 99%
“…Research in Atlas has resulted in novel distributed RDFS reasoning algorithms [18], and efficient strategies for RDF query processing on top of DHTs which cover one-time [15,9] and continuous queries [28]. We call one-time queries the standard queries asked in a typical RDF store (or a typical DBMS in general).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation